Isolation and antibiogram of Salmonella spp. from duck and pigeon in Dinajpur, Bangladesh - Rahman, Md. Moshiur; Rahman, Md. Mostafizer; Meher, Mirza Mienur; Khan, Md. Shafiqul Islam; Anower, A. K. M. Mostafa (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This research work was conducted for isolation of Salmonella spp. from duck and pigeon and assessment of antibiotic sensitivity patterns of the isolated Salmonella spp. Materials and methods: A total of 48 duck samples comprising of liver (n=16) spleen (n=16) and intestinal content (n=16) were collected from 16 ducks (8 sick and 8 dead). Similarly, 42 pigeon samples comprising of liver (n=14), spleen (n=14) and intestinal contents (n=14) were collected from 14 pigeons (7 sick and 7 dead). The samples were collected from the selected Duck and Pigeon farms at three Upazillas (sub-districts) in Dinajpur district, Bangladesh. The samples were subjected for isolation and identification of Salmonella spp. following standard bacteriological examinations such as cultural and morphological characteristics, biochemical properties and motility test. Commercially available antibiotic discs were used for the assesment of antibiotic resistant patterns by disc diffusion method. Results: Salmonella spp. could be isolated from 39.58% (n=19/48) duck and 28.57% (n=12/42) pigeon samples. The growth of colony with different characteristics in Brilliant Green agar, Nutrient agar, Salmonella-Shigella agar and Mac Conkey agar indicated positive results. Dextrose and mannitol were fermented and in Triple Sugar Iron (TSI) slant media, the isolates produced red color, yellow in butt with slightly black color. Positive result was found in Indole and Methyl Red media. The isolated Salmonella organisms were found to be highly sensitive to Azithromycin, Ciprofloxacin and Levofloxacin. Conclusion: Pigeons and ducks found in the study area may be the carrier of Salmonella spp. The farm should be checked periodically to know the status of Salmonella infection. Further study might be isolation and identification of Salmonella organism with detail genomic analysis and drug resistance. http://doi.org/10.5455/javar.2016.c177